Piperacillin-tazobactam induced hypokalaemia - Pandya, Amee D.; Gupta, Sapna; Malhotra, Supriya D.; Patel, Pankaj (International Journal of Basic & Clinical Pharmacology, 2018)
Electrolytes imbalance has been reported with the use of several antimicrobials in clinical scenarios. Piperacillin/tazobactam is a commonly used antibiotic with tolerable side effects and broad antimicrobial activity in general practice. Herein we report a case of a 27 year old male presented with Road Traffic Accident with depressed frontal bone fracture, fracture humerus and fracture of great toe complicated with Ventilator associated Pneumonia (VAP) who developed hypokalemia secondary to intravenous piperacillin-tazobactam. Upon withdrawal of the drug, serum potassium normalized in 2 days. There were no other underlying renal or hepatic illness and other causes of hypokalemia. Hypokalemia is a serious adverse effect of piperacillin-tazobactam and should be suspected while treating patients with this drug in clinical practice especially in Intensive Care Units (ICU). We concluded this causality as probable/likely category according to WHO-UMC Causality Categories.